Perception Analysis of Mutual Funds in Madhesh Province, Nepal - Karn, Dileep Lal (Tejganga Darpan, 2024)
The present empirical study explores the general perception of mutual funds in the Madhesh Province. A Mutual Fund is an aggregate fund comprising various investments such as stocks, bonds, and similar assets. It serves as a pool of funds primarily composed of several small domestic investors. The collected funds, also known as Basket Funds, are then invested in financial instruments such as stocks, bonds/debentures, government securities, and fixed deposits according to the objectives and scheme of such funds. Profits and losses are shared among investors in proportion to their investments. Investments in securities are spread across a wide cross-section of industries and sectors. A mutual fund is a trust that attracts the savings of a number of medium and small investors with a common financial goal. As the money collected from investors is invested in capital market instruments like shares, debentures, and other securities, the incomes and capital appreciations are distributed to its holders in proportion to the number of units owned by them. Diversification reduces the risk because all stocks may not move in the same direction or in the same proportion at the same time. Mutual funds in Nepal are regulated by the Securities Board of Nepal (SEBON). They can be issued, supervised, and managed only by entities/individuals fulfilling the criteria outlined in the Mutual Fund Regulation of 2067, as authorized by SEBON. The study analyzed that the majority of respondents are male youths, graduates, employees, and have limited familiarity with basket/mutual funds. They are influenced by tax incentives and expect high returns on investment.